KEBIJAKAN PEMERINTAH DALAM PENGENTASAN SISWA PUTUS SEKOLAH TINGKAT MENENGAH DI KABUPATEN BATANG - Arief Tri Atmoko; Achmad taufiq; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
AbstractOne of the problems that hinder the development of educational todayis Dropout. Dropout is a condition in which a student stops in running theeducation or no longer attending school for any reason. With high rates ofschool dropouts can cause other problems in all aspects of state next period. InBatang poor condition of high school is still seen from the Gross EnrollmentRate which is still below 50%, and is one of the causes of dropouts.This study used qualitative methods to understand and interpret themeaning of an event interaction of human behavior in certain situationsaccording to the researcher's own perspective. The data collection techniquesthat use in this study are interviews, and literature.The results showed that to overcome the problem of dropouts at the highschool in Batang central government, provincial governments and localgovernments work together to resolve the problem by issuing policies BSM,BKKM and BKTMB. In the policy implementation is based on the research isconsidered good enough to see the implementation of the policy variables. Thenfor the causes of dropout found 6 factors that cause students Delinquencyfactor, Loss Motivation Factor, Academic Factors, Economic Factors, SchoolsDistance Factor and Adaptation Capabilities Factors. However, governmentpolicies focused on economic factors alone.